Strategi Guru PAI dalam Menanamkan Moderasi Beragama di Era Digital melalui Integrasi RPP dan Pemanfaatan Media Digital - Aas Lutfiana; Novita Dwi Setyowati; Syaefudin Achmad (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2026)
Religious moderation has become a critical issue in education in the digital age, particularly due to the flood of religious information that does not always align with the values of tolerance. Junior high school students are vulnerable to exposure to exclusive religious ideologies without proper guidance. This study aims to describe the strategies employed by Islamic Education Islamic Education (PAI) in instilling religious moderation in ninth-grade students at State Junior High School 9 Salatiga. This study employs a qualitative approach with a descriptive design. Data were collected through interviews, observations, and documentation, then analyzed using an interactive analysis model and validated through triangulation. The results indicate that teachers’ strategies include integrating the value of moderation into lesson planning, using contextual case-based discussion methods, and utilizing digital media to enhance students’ religious literacy. These strategies have been proven to support a balanced, tolerant, and critical understanding of digital information. This study underscores the importance of religious education based on religious moderation in shaping students’ inclusive character in the digital age.